Confidential Audit of Perinatal Mortality in the Republic of Kazakhstan: A Pilot Study - Aizada Marat; Zaituna Khamidullina; Svetlana Muratbekova; Kulyash Jaxalykova; Bekturgan Karin; Nazerke Samatova; Umit Usmanova; Madina Sharipova; Aknur Kobetayeva; Milan Terzic; Yesbolat Sakko; Gulzhanat Aimagambetova (Medical Sciences)
Introduction: Perinatal mortality is labeled as the loss of fetuses at or beyond 22 weeks of gestation, deaths during labor and delivery, as well as early neonatal deaths. Appropriate medical care provided in the perinatal period is an integral indicator of high-quality medical care. Although developed countries managed to decrease perinatal mortality, it remains high in the developing world. This study aims to perform a confidential audit of perinatal mortality (CAPM) across Kazakhstani maternity hospitals. Methods: A descriptive, observational cross-sectional study was conducted from January 2024 to December 2024. The structure of the underlying causes of mortality in the antenatal, intranatal, and early neonatal periods among different maternity hospitals of the Republic of Kazakhstan was analyzed. Results: A total of 116 cases were assessed: 34 antenatal deaths, 6 intranatal, and 76 early neonatal. Most deaths occurred on the second day post-delivery. The analysis revealed that 93% of cases fell into categories indicating substandard or potentially inadequate care (categories 2 and 3). Intraventricular hemorrhage and sepsis emerged as leading causes of neonatal death. Among antenatal and intranatal deaths, significant proportions were associated with comorbid maternal conditions, insufficient antenatal visits, and inadequate perinatal support. Conclusions: CAPM proves to be a critical tool for identifying systemic gaps and guiding improvements in maternity services without attributing blame to health professionals. Findings underscore that many perinatal deaths could have been avoided with timely, evidence-based interventions across antenatal and neonatal care. Broader implementation and institutionalization of CAPM in Kazakhstan could lead to measurable reductions in perinatal mortality and improvements in maternal/newborn care outcomes. Factors such as preconception planning, improving the health of reproductive-age women, administration of folic acid, and reducing primary cesarean sections could assist in achieving the reduction in the perinatal mortality rate.